A spectral load model for pedestrian excitation including vertical human-structure interaction. (1st February 2018) - Bassoli, Elisa; Van Nimmen, Katrien; Vincenzi, Loris; Van den Broeck, Peter
Highlights: Human-induced vibrations for a wide range of footbridge and crowd parameters. Spectral load model for pedestrian actions in unrestricted and crowded conditions. Vertical mechanical interaction between pedestrians and the supporting structure. Observed cases where HSI causes an increased structural response. Abstract: This paper is focused on the evaluation of the structural response to vertical pedestrian excitation for a wide range of footbridge and crowd parameters. A spectral load model for pedestrian-induced forces proposed in literature is adopted. The model accounts for the randomness in the human excitation as well as the increased correlation among pedestrians with pedestrian density. Therefore, it can be applied for the vibration serviceability analysis of footbridges in unrestricted and crowded traffic conditions. With the purpose of predicting the structural response for a wide range of natural frequencies, an extension of the model to account for the contribution of the first three harmonics of the walking load is proposed. To allow for a more accurate prediction of the maximum response, the present study in addition accounts for the vertical mechanical interaction between pedestrians and the supporting structure. Finally, the impact of human-structure interaction (HSI) on the structural response is investigated. By applying the methods of linear random dynamics, the maximum dynamic response of the footbridge is evaluated based on an analytical formulation of the load and the frequency response function (FRF) of the coupled crowd-structure system. The most significant HSI-effect is in the increase of the effective damping ratio of the coupled crowd-structure system that leads to a reduction of the structural response. However, in some cases the shift in frequency of the coupled crowd-structure system results into a higher structural response when HSI-effects are accounted for.